Resección laparoscópica de 13 teratomas ováricos y un quiste simple en una misma paciente: reporte de caso Laparoscopic resection of 13 ovarian teratomas and a simple cyst in the same patient: a case report - Aníbal Mesa; Victoria E Ramos; Liana D Bolívar; Juan D Castañeda; José Fernando De los Ríos (Federación Colombiana de Obstetricia y Ginecología, 2007)
Se describe el caso de una mujer que consultó por dolor pélvico. Tenía una ecografía transvaginal que reportaba teratomas bilaterales de ovario. Fue llevada a cirugía laparoscópica durante la cual se extirparon 7 teratomas y 1 quiste folicular simple del ovario derecho y se realizó salpingooforectomía izquierda, encontrando 6 teratomas intraováricos. Los objetivos de esta publicación son reportar un caso atípico de múltiples lesiones ováricas sincrónicas y discutir algunos aspectos controversiales del manejo de los teratomas por laparoscopia. This paper describes the case of a woman who complained of pelvic pain. She underwent a transvaginal ultrasound which revealed the presence of bilateral ovarian teratomas. She then underwent a laparoscopy in which 7 teratomas and one simple cyst were found and resected from the right ovary; 6 additional teratomas were found within the ovary following left-hand side salpingoophorectomy. This case is reported to increase the body of literature concerning multiple ovarian lesions and because no other reports about such a large amount of multiple teratomas which have been handled by laparoscopy despite the size and the number of the tumors could be found after conducting extensive research.